Implementation Of Green Human Resource Management To Improve Sustainable Performance In The Hotel And Tourism Industry In Medan City - Susi Marta Tambunan; Riza Afni; Rianto Manurung (SEAN Institute, 2024)
The implementation of Green Human Resource Management (GHRM) has become a key strategy in enhancing sustainable performance in the hotel and tourism sector. This research aims to analyze the impact of GHRM on sustainable performance in the hotel and tourism industry in Medan City. The research method uses a quantitative approach with data collection through surveys of managers and employees from hotels and tourist destinations in Medan City. The results show that the implementation of GHRM practices, such as environmentally friendly recruitment, environmental awareness training, green performance management, and employee involvement in environmental initiatives, significantly contributes to improvements in operational efficiency, reduction of environmental impacts, and long-term sustainability achievements. Moreover, this approach also enhances employee motivation to support environmentally friendly practices, creates added value for the organization, and attracts the attention of environmentally-conscious tourists. The conclusion of this study emphasizes that the adoption of GHRM can be a strategic solution to support the sustainability of the hotel and tourism industry in Medan City, while also making a positive contribution to environmentally friendly economic development.